PKM Pembuatan “CAPCIN WARTH” Bagi Masyarakat di Kecamatan Rappocini - Ratnah S; Nurjannah Nurjannah; Mustari Mustari; Nur Arisah; Sitti Hajerah Hasyim (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Capocino Cincau product is one of the innovations in the beverage industry that combines the deliciousness of cappuccino with the pleasure and benefits of cincau. This community service aims to increase the income value of the community by innovating one of the drinks, namely Capocino Cincau, into an attractive drink with an affordable price, namely